Prevalence of Microalbuminuria and its Association with Left Ventricular Hypertrophy (LVH), Ischemic Heart Disease (IHD), Retinopathy, and Stroke in Hypertension (Journal of Rangpur Medical College, 2023)
Background: Hypertension is a growing issue of public health problem of the adult population in both developed as well as developing world, is a serious medical condition that significantly increases the risks of heart, brain, kidney, and other diseases. There is a strong association between Microalbuminuria (MA) and hypertension. Microalbuminuria (MA) is the independent risk factor for developing cardiovascular and cerebrovascular morbidity and mortality in hypertension, suggesting that microalbuminuria (MA) could be a useful marker to assess the risk management of cardiovascular disease and renal disease.Objective: To assess the frequency of microalbuminuria in hypertension and to evaluate its association with left ventricular hypertrophy (LVH), ischemic heart disease (IHD), retinopathy, and stroke.Methods: This cross-sectional descriptive study was conducted at the Hypertension & Research Centre, Rangpur from January 2010 to January 2012. A total of 75 hypertensives without diabetes mellitus and/or other conditions causing microalbuminuria were purposively selected. Urine albumin was assessed and microalbuminuria was defined as albumin excretion between 20-200 microg/min. The relationship of microalbuminuria with the duration, severity, body mass index (BMI), lipid profile, and target organ damage (TOD) like left ventricular hypertrophy (LVH), ischemic heart disease (IHD), hypertensive retinopathy, and stroke was assessed by univariate analysis.Results: The patients were in between the age of 20-79 years with mean age of 52.98±12.2. Out of 75 subjects, 47 (62.7%) patients were male and 28 (37.3%) were female. Of the study group, 53 patients had stage 1 and 22 patients had stage 2 hypertension. Among the stage-1 hypertensive (53), 5 patients had microalbuminuria and 6 patients had microalbuminuria in stage-2 hypertensive (22) (p=0.047). Microalbuminuria was significantly higher in those with longer duration and greater severity of hypertension (p =0.039). Older age (p =0.008), and adverse lipid profile (p =0.003) were the other identifiable risk factors for microalbuminuria. Stroke (OR=9.77), echocardiography-proven LVH (OR=6.25), ECG and/or echocardiographyproven IHD (OR=8.71) and hypertensive retinopathy (OR=4.14) were significantly higher in those with microalbuminuria.Conclusion: The prevalence of microalbuminuria in hypertensive subjects is high and patients with microalbuminuria have high odds of developing TOD like stroke, LVH, IHD, and hypertensive retinopathy. So the early detection of microalbuminuria in hypertensive as well as prompt treatment may reduce the burden of TOD.J Rang Med Col. March 2023; Vol. 8, No. 2:3-10